Structural Basis for the Immunogenicity of the C-Terminus of VP1 of Echovirus 3 Revealed by the Binding of a Neutralizing Antibody - Shuai Qi; Wangjun Fu; Jinyan Fan; Li Zhang; Binyang Zheng; Kang Wang; Xiangxi Wang; Ling Zhu; Xinjian Li; Yuxia Zhang (Viruses, 2022)
Echovirus 3 (E3), a serotype of human enterovirus B (HEV-B), causes severe diseases in infants. Here, we determined the structures of E3 with a monoclonal antibody (MAb) 6D10 by cryo-EM to comprehensively understand the specificities and the immunological characteristic of this serotype. The solved cryo-EM structures of the F-, A-, and E-particles of E3 bound with 6D10 revealed the structural features of the virus–antibody interface. Importantly, the structures of E-particles bound with 6D10 revealed for the first time the nature of the C-terminus of VP1 for HEV-Bs at the structural level. The highly immunogenic nature of this region in the E-particles provides new strategies for vaccine development for HEV-Bs.